Low KV-low contrast medium dose one-stop dual source CT high pitch integrated coronary-carotid-cerebral-aortic CTA improves image quality and reduces both radiation and contrast medium doses - Meng Wang; Chao Zheng; Lin Yang; Juan Su; Bo Wang; JieXin Sheng (European Journal of Radiology Open)
Rationale and objectives: To evaluate the impact of low dose-low contrast medium injection protocol on radiation dose and image quality of one-stop dual source high pitch integrated coronary -carotid -cerebral- aortic CTA. Methods: A total of 211 non-obese patients, consisting of 44 females with an average age of 59 years, were split into two groups: low dose group (LD group n = 136) and routine dose group (RD group n = 75). Noise, attenuation, signal to noise ratio (SNR), and contrast to noise ratio (CNR) were compared between the groups by setting region of interest (ROI) in target vessels to evaluate objective image quality. Two radiologists assessed subjective image quality using the 5-point scale. volumetric CT dose index (CTDIvol), dose length production (DLP), and effective radiation dose (ED) were compared, while contrast medium (CM) dose was assessed by CM volume and iodine uptake (IU). Results: Both radiation and CM dose were significantly reduced in the LD group compared with the RD group, DLP and ED were reduced by 51 %, and CM volume and IU were reduced by 13 % (all p < 0.05). Attenuation and noise were higher, while SNR and CNR were close to or slightly higher in the LD group compared with the RD group. The LD group had higher subjective image quality scores while all scores in the two groups satisfied the diagnostic requirements. Conclusion: Low-kV, low-CM one-stop dual-source high-pitch integrated coronary-carotid-cerebral-aortic CTA can ensure image quality while significantly reducing the doses of contrast medium and radiation